1989
DOI: 10.1159/000215913
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Degradation of Platelet-Activating Factor in Serum from Diabetic Patients

Abstract: The degradation of platelet-activating factor (PAF) and lipid concentrations were measured in sera from 20 patients with insulin-dependent diabetes mellitus and from 20 age- and sex-matched healthy volunteers. The PAF-degrading capacity as well as triglycerides and total and very low density and low-density lipoprotein cholesterol were found to be significantly increased in the patients group, whereas the difference observed in high-density lipoprotein cholesterol was statistically nonsignificant. There were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
7

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
5
0
7
Order By: Relevance
“…The results of our study showed that the serum PAF-AH activity in heterozygous FH patients is significantly higher than that of normolipidaemic control subjects. Changes in the activity of serum PAF-AH have been associated with several human diseases [27][28][29], and some studies have demonstrated the existence of a good correlation between PAF-AH activity and disease activity [30]. However, as has been reported, there is a marked excess of enzyme in serum under basal conditions, while a reduction in the enzyme activity by as much as 50% would not increase the half-life of PAF in blood [31].…”
Section: Discussionmentioning
confidence: 96%
“…The results of our study showed that the serum PAF-AH activity in heterozygous FH patients is significantly higher than that of normolipidaemic control subjects. Changes in the activity of serum PAF-AH have been associated with several human diseases [27][28][29], and some studies have demonstrated the existence of a good correlation between PAF-AH activity and disease activity [30]. However, as has been reported, there is a marked excess of enzyme in serum under basal conditions, while a reduction in the enzyme activity by as much as 50% would not increase the half-life of PAF in blood [31].…”
Section: Discussionmentioning
confidence: 96%
“…The plasma activity of this enzyme has been shown to increase during the "stress" reaction of the lizard (7). in patients with ischemic cerebrovascular disease (8), with insulin-dependent diabetes mellitus (9), in spontaneous hypertensive rats (lo), and in Caucasian males with hypertension (1). The plasma activity is decreased in asthmatic children (1 I ) and in the maternal plasma during the latter stages of pregnancy (12).…”
mentioning
confidence: 99%
“…The pancreas may produce PAF under normal conditions, but a relation between PAF signalling and the secretion of pancreatic hormones and insulin is not yet defined. PAF acetylhydrolase activity was increased in plasma from patients with diabetes mellitus [41]. and in urine from patients with diabetic nephropathy [49].…”
Section: Diabetic Diseasesmentioning
confidence: 98%